Analysis of the clinicopathological features and prognostic factors in 734 cases of Chinese Hui and Han patients with adenocarcinoma of the esophagogastric junction. (September 2018) - Cao, Jianqiao; Yang, Ting; Wang, Guanhua; Zhang, Hongfei; You, Yanjie; Chen, Jing; Yang, Jingwen; Yang, Wenjun
Abstract: Objective: To explore the clinicopathological features and prognostic factors of 734 cases of Chinese Hui and Han patients with adenocarcinoma of the esophagogastric junction (AEG). Methods: In total, 734 patients were confirmed to have AEG by gastroscopy and pathology at the General Hospital of Ningxia Medical University between January 2002 and December 2012. Univariate and multivariate analyses of demographic, clinicopathological, and prognostic data were performed. Results: In total, 734 AEG patients underwent surgical intervention, including 169 Hui patients and 565 Han patients. The male to female ratio was 9.5:1 in Hui patients and 6.4:1 in Han patients, and the average age in both groups was approximately 61 years. The Han patients were more likely to have a cigarette smoking history and an alcohol consumption history than the Hui patients (58.8% vs. 29.4%, p = 0.000; 45.8% vs. 14.6%, p = 0.000). The 5-year survival rate in the Hui and Han patients was 54.3% and 39.9%, respectively (p = 0.024). Age (p = 0.005), sex (p = 0.015), pathologic T stage (p = 0.056), pathologic N stage (p = 0.000), pathologic M stage (p = 0.001), number of resected lymph nodes (p = 0.001) and adjuvant chemoradiotherapy (p = 0.002) were significant independent prognostic factors. Conclusion: The AEG patients were primarily male and elderly in both Hui and Han groups with the prognosis of Hui patients better than Han patients. Age, sex, pathologic T3-4 stage, pathologic N stage, pathologic M stage, number of resected lymph nodes, and adjuvant chemoradiotherapy were significant independent factors predictive of the prognosis of AEG in both groups. Highlights: The AEG patients were primarily elderly males in both Hui and Han groups. Han patients had more cigarette smokers and alcohol drinkers than Hui patients. Most AEG patients were suffered from advanced pathologic stages with poor prognosis. The prognosis of Hui patients was better than that of Han patients.